قياس نمو إنتاجية الموارد في القطاع الزراعي في الجزائر للفترة 1990-2016 - ضو, نصر; لبزة, هشام (University of Eloued جامعة الوادي, 2019)
من خلال هذه الدراسة سوف نتعرف على مساهمة كل عنصر من عناصر الإنتاج الرئيسية في حجم الإنتاج الزراعي المتحقق وذلك عن طريق دراسة العلاقة الدالية بين قيمة الإنتاج الزراعي في الجزائر والمتغيرات التي تؤثر فيه كالعمل ورأس المال العام ، ورأس المال الخاص والأرض ، وقياس مساهمة ونمو إنتاج الموارد في القطاع الزراعي الجزائري في المدة (1990-2016). تنطلق الدراسة من فرضية رئيسية مفادها انه هناك تحسنا في معدل نمو المحاصيل الزراعية في الجزائر ، وهو نتاج توجه الحكومة الجزائرية الى سياسة التنويع الاقتصادي، ولقد استخدمنا في دراستنا دالة الإنتاج التجميعية وهي من أكثر الأساليب شيوعا في دراسات نمو الإنتاجية ، وتشير معظم الدراسات إلى أن استعمال دالة الإنتاج التجميعية يعطي تقديرا جيدا ومعقولا للإنتاجية ، ويتم افتراض تجانس دوال الإنتاج من الدرجة الأولى ، ويقال انها متجانسة خطيا ومن أشهر دوال الانتاج المتجانسة الواسعة الاستعمال في قياس مصادر النمو هي دالة كوب-دوغلاس ، والتي يمكن استعمالها كدالة انتاج تجميعية متعددة الحدود في القطاع الزراعي .أن هناك نمو في الإنتاج الزراعي في الجزائر لكن ليس بالمستوى المطلوب والذي كان مخطط له في برنامج الدعم الحكومي للقطاع الفلاحي . Summary: Through this study will identify the contribution of each element of the main production in agricultural production volume achieved by examining the relationship between the value of agricultural production in vine Algeria and the variables Affecting it as work and public capital and private capital and the Earth, and measure the contribution of resource production and growth in the agricultural sector in length (1990-2016).Study of the major premise starts that there is an improvement in the rate of growth of agricultural crops in Algeria, the Algerian Government is the result of a policy of economic diversification,And we've used in our study of aggregate production function and is the most common method in studies of productivity growth, most studies indicate that the use of aggregate production function gives a good and reasonable estimate of productivity,The homogeneity of the first-order production functions is assumed to be homogeneous and linear. One of the most common homogenous production functions used in the measurement of growth sources is the Kop-Douglas function, which can be used as a multimodal aggregate production function in the agricultural sector. That there is growth in agricultural production in Algeria but not the level required and which was planned in the program of government support for the agricultural sector.
الملتقى الدولي السابع حول اقتصاديات الإنتاج الزراعي في ظل خصوصيات المناطق الزراعية في الجزائر والدول العربية 30- 31 أكتوبر 2019 كلية العلوم الاقتصادية والتجارية وعلوم التسيير جامعة الشهيد حمه لخضر الوادي
Keywords: الزراعة، الانتاجية ، الجزائر ، النمو ، كوب دوغلاس; Agriculture, productivity, Algeria, growth, cup Douglas.